Le suffrage universel et le problème de la souveraineté du peuple. - Brousse, P. (Genève : [s.n.], 1874)
Collectie Vrijzinnige Werkmansbibliotheek
Frans
Monografie
Keywords: Vrijzinnige Werkmansbibliotheek